Kearifan Lokal Masyarakat dalam Mengelolah Lahan Jagung (Studi Sosial Ekonomi Desa Tala Kecamatan Amalatu Kabupaten Seram Bagian Barat) - Levin Kristin Kewere; Melianus Salakory; Ferdinad Salomo Leuwol (GEOFORUM, 2025)
Local wisdom is inherited knowledge that guides communities in managing natural resources, including agricultural land. This study aims to identify forms of local wisdom practiced by the people of Tala Village, Amalatu District, West Seram Regency, in managing corn land as a food source and household economic support. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation, involving 10 informants purposively selected from a population of 20. The findings reveal that the community applies traditional management strategies from land preparation, seed selection, planting, maintenance, to harvesting and distribution. These practices maintain soil fertility through simple methods such as burning weeds for natural fertilizer, determining planting time based on local climate, and utilizing corn cobs as alternative fuel. The study concludes that these practices not only enhance food security and community welfare but also reflect ecological adaptation values relevant to sustainable development. The implications highlight the need for regional policy support in preserving local wisdom and recommend integrating traditional knowledge with modern agricultural technology to strengthen productivity and food resilience